Synthesis and Characterization of Iron Oxide Nanoparticles by Open Vessel Ageing Process - Majeed, Najwa Saber; Naji, Duaa Mahammed (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
Nano-crystalline iron oxide nanoparticles (magnetite) was synthesized by open vessel ageing process. The iron chloride solution was prepared by mixing deionized water and iron chloride tetrahydrate. The product was characterized by X-Ray, Surface area and pore volume by Brunauer-Emmet-Teller, Atomic Force Microscope (AFM) and Fourier Transform Infrared Spectroscopy(FTIR) . The results showed that the XRD in compatibility of the prepared iron oxide (magnetite) with the general structure of standard iron oxide, and in Fourier Transform Infrared Spectroscopy, it is strong crests in 586 bands, because of the expansion vibration manner related to the metal oxygen absorption band (Fe–O bonds in the crystals of iron oxide). The results show that the prepared nano iron oxide is with average crystal size 75.92 nm, surface area was 85.97 m2/g and the pore volume was found equal to 0.1566 cm3/